2023
DOI: 10.1200/op.21.00815
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparative Effectiveness Trial of Multidisciplinary Lung Cancer Care Within a Community-Based Health Care System

Abstract: PURPOSE: Multidisciplinary lung cancer care is assumed to improve care delivery by increasing transparency, objectivity, and shared decision making; however, there is a lack of high-level evidence demonstrating its benefits, especially in community-based health care systems. We used implementation and team science principles to establish a colocated multidisciplinary lung cancer clinic in a large community-based health care system and evaluated patient experience and outcomes within and outside this clinic. ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…We defined the MDC cohort strictly as patients whose care had been prospectively reviewed in a structured Multidisciplinary Thoracic Oncology Conference which we implemented with rigorous Team Science principles. 14 , 18 , 19 , 20 , 21 , 22 Only such patients were captured in the MDC database. Patients outside this structured program were categorized as non-program-based care recipients, irrespective of discussion in other forums within or outside BMHCC.…”
Section: Methodsmentioning
confidence: 99%
“…We defined the MDC cohort strictly as patients whose care had been prospectively reviewed in a structured Multidisciplinary Thoracic Oncology Conference which we implemented with rigorous Team Science principles. 14 , 18 , 19 , 20 , 21 , 22 Only such patients were captured in the MDC database. Patients outside this structured program were categorized as non-program-based care recipients, irrespective of discussion in other forums within or outside BMHCC.…”
Section: Methodsmentioning
confidence: 99%
“…Many advantages, and some disadvantages, are associated with the multidisciplinary meeting model [ 26 ]. MDTs can evaluate diagnostic and treatment options with a decision-making process more adherent to cancer guidelines [ 27 ] which could increase patient survival rates [ 1 ], although some authors demonstrated that improved care processes due to MDT activity do not necessarily result in better clinical outcomes [ 3 , 27 29 ]. MDTs also increase patient satisfaction and quality of life.…”
Section: Lung Cancer Care Modelsmentioning
confidence: 99%
“…The literature describes three main approaches for lung cancer care: the sequential referral model, the multidisciplinary meeting model, and the multidisciplinary clinic model (Table 1) [2]. The difference depends on if multidisciplinary involvement is continuous throughout the patient pathway or whether it is fragmented or "on demand" [15].…”
Section: Lung Cancer Care Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that there is a premium on coordination with the core member(s) of a team 27 and among core team representatives in more complex MTS arrangements, such as AYA multidisciplinary teams (Wolfson), 28 main and community affiliate sites in the same health care system (Roberts). 29,30 Mechanisms such as the interoperability of health information technology 31 and dedicated program coordinators with integrated screening tools have shown promise (Fleege), 32 whereas the colocation of multidisciplinary care versus serial care (Majumdar, Smeltzer) 33,34 and other structural arrangements (O'Malley) 35 have yielded mixed results.…”
Section: What Needs To Be Shared By Whom?mentioning
confidence: 99%